2012
DOI: 10.1007/s00464-012-2303-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of transanal minimally invasive surgery for mid-rectal lesions

Abstract: TAMIS seems to be a feasible and safe treatment option for lesions located in the mid rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 17 publications
2
55
0
3
Order By: Relevance
“…The most critical issue is suturing. Other authors recently reported difficulties in repairing the excision defect so that different methods have been proposed, including use of an endo-GIA stapler [9], intracorporeal suture-tying [11,12], or interrupted sutures with extracorporeal knots that are secured with a knot-pusher [10]. In any case, the maneuver is very challenging and an ideal technique has not been described yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most critical issue is suturing. Other authors recently reported difficulties in repairing the excision defect so that different methods have been proposed, including use of an endo-GIA stapler [9], intracorporeal suture-tying [11,12], or interrupted sutures with extracorporeal knots that are secured with a knot-pusher [10]. In any case, the maneuver is very challenging and an ideal technique has not been described yet.…”
Section: Discussionmentioning
confidence: 99%
“…as TransAnal Mini-Invasive Surgery (TAMIS) [9,10], Transanal Single-Port Microsurgery (TSPM) [11], Transanal Endoscopic Video-Assisted surgery (TEVA) [12], and SILSTEM [13], has been adopted. In all these procedures, a single-incision laparoscopic surgery port is introduced into the anal canal, followed by transanal excision using standard laparoscopic instruments.…”
mentioning
confidence: 99%
“…TAMIS, which was a novel approach, was first reported by Atallah et al in 2010 (13). This was followed by various reports of the use of TAMIS in an increasing number of cases, using similar platforms with acceptable outcomes (18)(19)(20)(21). TAMIS using a GelPOINT ® Path provides excellent exposure of the operative field, due to its high-definition flexible tip camera and constant gas dilatation, The depth of T1 invasion is indicated (as x µm); well, well-differentiated adenocarcinoma; mod, moderately differentiated adenocarcinoma; ly, lymphatic invasion; v, venous invasion; F, female; M, male.…”
Section: Discussionmentioning
confidence: 99%
“…С учетом того, что способ ТЭМ успешно используется во всем мире для хирургии добро-качественных и злокачественных новообразова-ний прямой кишки, в последние годы появился повышенный интерес к применению этого способа для реверсивного выделения опухоли и прямой кишки при злокачественных новооб-разованиях с удалением макропрепарата через естественные анатомические отверстия [45,46]. Трансанальное снизу вверх выделение опухоли и прямой кишки с использованием ТЭМ имеет ряд преимуществ:…”
Section: трансанальная мезоректумэктомияunclassified